Teachers’ Perceptions about Language Learning Difficulties in English as a Foreign Language EFL Classes - Haggag, Haggag Mohamed; Bakr, Eman Mohy-Eldeen (European Scientific Journal, ESJ, 2020)
The research aimed at verifying English language teachers’ perceptions about English language learning difficulties in their classes. Using a descriptive analytical approach, it utilized a questionnaire which included (60) items which were divided over four parts; the first was about the basic concepts, the second was about the intervention techniques, the third included class barriers while the fourth was about class assessment techniques. The second instrument is an online reflection journal to record participants’ views about language learning difficulties. The participants (N. 99) were English language teachers from different stages at The Red Sea Governorate in Egypt. Following a descriptive analytical research design, the research utilized the instruments to record the results and interpret them in the light of its hypotheses. Results showed that there was a strong correlation between participants’ concepts over the four parts of the questionnaire (basic concepts, intervention techniques, class barriers and assessment techniques. Results also showed that there were significant mean differences between participant’s scores in the four parts of the questionnaire favoring the concepts part. Recommendations of the research included integrating language learning difficulties modules in both pre-service and in-service teachers’ education and training programs as well as highlighting intervention techniques in EFL curricula as well as LD assessment procedures and techniques.